Results of injection sclerotherapy with bleomycin in pediatric lymphatic malformations - Vipan Kumar; Subhasis Roy Choudhury; Partap Singh Yadav; Vikram Khanna; Amit Gupta; Rajiv Chadha; Rama Anand (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of the study was to evaluate the results of injection sclerotherapy with bleomycin in pediatric patients with lymphatic malformations. Materials and Methods: In this prospective cohort study, all consenting pediatric patients with macrocystic lymphatic malformations were managed with injection bleomycin sclerotherapy (0.5 mg/kg, not exceeding 5 mg at a time) under ultrasound (US) guidance. After aspirating the cyst fluid bleomycin was instilled intralesionally in a ratio of 5:1 (aspirated cyst fluid volume: diluted bleomycin solution volume). Patients were reassessed at three weekly intervals. The response to therapy was assessed clinically as well as by size and volume on ultrasound Doppler study. The response was classified as excellent response, i.e., complete regression, good response >50% regression, and poor response <50% regression. Results: Sixty patients with lymphatic malformations were enrolled in the study, the mean age was 3.22 years, and the male-to-female was 2.5:1. The most common site of lesion was in the neck (43.3%), followed by the axilla (15%) and flank (8.3%). The responses were excellent, good, and poor in 43 (71.6%), 12 (20%), and five (8.3%) patients, respectively. Two patients underwent surgical excision of the residual lesion. Complications noted were fever in six, local pain in five, and residual lesion in three patients. Conclusion: Sclerotherapy with bleomycin is simple, safe, and effective in the first line of management for macrocystic lymphatic malformations in children.